GIS-material for the archaeological project: New remains by Bergsvägen - New local plan for petrol stations - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to local plans concerning new petrol stations in northwest Tornby, Linköping municipality, the Swedish National Heritage Board's Contract Archaeology Division, UV Öst has performed an assessment, phase 2. Along a stretch of somewhat higher ground sloping slightly to the west, in the south-east part of the area, nine prehistoric features were found, such as hearths or graves, post holes and cultural layers. Several of the features contained great amounts of fire cracked stones, soot and charcoal. The features have been examined on the surface but not excavated. A few finds of burnt bones and worked quartz were also made. The area containing archaeological remains has been delimited. No archaeological remnants were found in the rest of the area.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the archaeological assessment was to determine if the area contains any archaeological remains protected by law.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Inför detaljplanering för nya bensinstationer i NV Tornby, Linköpings kommun, har Riksantikvarieämbetet UV Öst utfört en arkeologisk utredning, etapp 2. På en västsluttning utmed en svag förhöjning i områdets SÖ del påträffades 9 förhistoriska anläggningar i form av härdar eller gravar, stolphål och kulturlager. Rikligt med skärvsten, sot och kol påträffades i flera av dem. Anläggningarna har ytundersökts men inte grävts bort. Ett par fynd av brända ben och bearbetad kvarts gjordes. Området där förhistoriska anläggningar påträffades har avgränsats. På området i övrigt påträffades inga förhistoriska anläggningar.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med utredningen var att avgöra om området innehåller lagskyddade fornlämningar.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Nya lämningar vid Bergsvägen - Ny detaljplan gällande bensinstationer
Keywords: stone age; stenålder; Bronze Age; bronsålder; Iron Age; järnålder; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi